Considerations for a Resource Allocation Framework for Intensive Care Units and Acute Care: A Qualitative Study Exploring the Experiences of Equity-Deserving Groups During the COVID-19 Demand Surge and Triage-Avoidant Strategies - Shorting, Taylor; Rastogi, Jaya; Bensimon, Cécile; Virani, Alice; Smith, Maxwell; Oczkowski, Simon; Godkin, Dianne; Warren, Marika; Valiani, Sabira; King, Judy; Downar, James; Isenberg, Sarina (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
During COVID-19, most intensive care units (ICUs) in Canada implemented strategies to manage a surge in demand for critical care to avoid turning people away, termed “triage-avoidant strategies.” These strategies, including redeploying non-ICU staff to the ICU to increase patient capacity, and transferring people over long distances to available beds, may have caused negative consequences for patients, healthcare staff, and equity-deserving groups. This study explores the perspectives of equity-deserving groups and organizations on triage-avoidant strategies during COVID-19, examined organization-specific responses, and identified system-level recommendations to improve equity, access, and preparedness. A qualitative descriptive study was conducted between July and December 2023 across five provinces in Canada. Participants, including staff from organizations serving equity-deserving groups, as well as government and healthcare representatives, were recruited through professional networks and snowball sampling. A semi-structured interview guide was used to elicit perspectives, which were then analyzed inductively using thematic analysis. 23 individuals from Ontario (n=12), British Columbia (n=4), Saskatchewan (n=4), Nova Scotia (n=2) and New Brunswick (n=1) participated. 15 participants (65%) identified as persons of colour or among equity-deserving groups; 13 (57%) participants worked within organizations representing decision-makers, clinicians, and/or equity-deserving groups. We identified three themes: 1) Triage-avoidant strategies were perceived to have disproportionately harmful effects on equity-deserving groups and healthcare providers; 2) organizations acted to mitigate effects of triage-avoidant strategies; and 3) various system-level actions could help mitigate the perceived effects of these strategies in future surges in demand. This study contributes to the literature by incorporating perspectives of representatives from diverse organizations and equity-deserving groups on how triage-avoidant strategies disproportionately harmed the populations they serve. Our findings can inform the development/implementation of triage-avoidant strategies that mitigate the perceived harmful effects on decision-makers, clinicians, and equity-deserving groups, while promoting equitable care.